Electronically tunable current-mode universal filter with three-input single-output - Kumngern, Montree; Torteanchai, Usa; Dejhan, Kobchai (My University, 2010)
A new current-controlled current-mode universal filter with three inputs and single output employing two translinear current conveyor and two grounded capacitors is presented. The proposed circuit provides low-pass, band-pass, high-pass, bandstop and all-pass current responses from the same configuration at a high impedance terminal. The filter also offers independent electronic control of the natural frequency and quality factor through adjusting the bias current of the translinear current conveyor. The characteristics of the proposed filter are simulated using PSPICE to confirm the theory. © 2010 IEEE.
Keywords: Current-mode; Translinear conveyor; Universal filter